2004
DOI: 10.1007/s00787-004-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Treating depressive symptoms in schoolchildren

Abstract: Although studies on sub-threshold depression in childhood and adolescence have demonstrated an at risk profile that merits further attention, only few investigators examined the impact of therapy with these children. In this study, twenty elementary schoolchildren (aged 10-12) with moderate depressive symptoms were randomly assigned to an eighteen-session cognitive-behavioural treatment programme or to a waiting list (WL) control group (= Study 1). The key components of the programme "Taking Action" used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The mean age of the participants was 10.5 years (range 9.2 -12.7 years). In six studies, all participants were , 13 years of age (Asarnow et al, 2002;Butler et al, 1980;de Cuyper et al, 2004;Liddle & Spence, 1990;Stark et al, 1987;Weisz et al, 1997). In two studies, there were participants who were up to 14 years of age (Kahn & Kehle, 1990;Nelson, Barnard, & Cain, 2003).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The mean age of the participants was 10.5 years (range 9.2 -12.7 years). In six studies, all participants were , 13 years of age (Asarnow et al, 2002;Butler et al, 1980;de Cuyper et al, 2004;Liddle & Spence, 1990;Stark et al, 1987;Weisz et al, 1997). In two studies, there were participants who were up to 14 years of age (Kahn & Kehle, 1990;Nelson, Barnard, & Cain, 2003).…”
Section: Resultsmentioning
confidence: 98%
“…A recent meta-analysis concluded that CBT and interpersonal therapy are probably efficacious when compared to no treatment, but the authors qualified their findings by noting that it was likely that the effect seen in their analysis was restricted to children 12 -18 years of age (Watanabe et al, 2007). Furthermore, in most published studies the children have not been diagnosed (Asarnow, Scott, & Mintz, 2002;Butler et al, 1980;de Cuyper, Timbremont, Braet, De Backer, & Wullaert, 2004;Liddle & Spence, 1990;Stark et al, 1987;Weisz, Thurber, Sweeney, Proffitt, & LeGagnoux, 1997) and in a number of studies prevention samples have been included (e.g., Gillham, Reivich, Jaycox, & Seligman, 1995;Jaycox, Reivich, Gillham, & Seligman, 1994). Including prevention samples, however, may hamper the generalizations to be made, as they seem to have greater gains from treatment as compared to clinical samples (Klein, Jacobs, & Reinecke, 2007).…”
mentioning
confidence: 87%
“…128 General well-being data were obtained solely from child self-report and in only three studies. 51,87,107 Self-esteem data were collected by child self-report in 10 studies 51,57,[60][61][62][63][64]106,[129][130][131]134,136 and from a parent in one study. [129][130][131] Full details of the outcome measures extracted for each study can be found in Appendix 6; for a summary of the number of outcome measures of each type, see Table 4.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The different components of CBT --including affective regulation, problem-solving, cognitive restructuring, and engaging in enjoyable activities --tailored to school-age children appear promising [89]. Other forms of therapies using group format appear feasible and efficacious as a treatment of mild to moderate prepubertal depression [90].…”
Section: Predictors Of Treatment Outcomementioning
confidence: 99%
“…CBT has been adapted for use in school-age children [89][90][91]. The different components of CBT --including affective regulation, problem-solving, cognitive restructuring, and engaging in enjoyable activities --tailored to school-age children appear promising [89].…”
Section: Predictors Of Treatment Outcomementioning
confidence: 99%